1999
DOI: 10.1165/ajrcmb.21.2.3489
|View full text |Cite
|
Sign up to set email alerts
|

Role of Arachidonyl Triglycerides within Lipid Bodies in Eicosanoid Formation by Human Polymorphonuclear Cells

Abstract: Increasing evidence suggests that the subcellular and glycerolipid localization of esterified arachidonic acid (AA) is a key factor in regulating its availability to lipases. The goal of the current study was to determine the potential of AA stored in triglycerides (TG) to serve as a substrate for lipases and 5-lipoxygenase during neutrophil (polymorphonuclear leukocytes, PMN) activation. PMN containing high concentrations of AA in TG were generated by culturing PMN in vitro with high concentrations of exogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 21 publications
5
20
0
Order By: Relevance
“…Interestingly, EETs influence neutrophil adherence in the low micromolar range (Pratt et al 2002). Since both arachidonate and linoleate are present in relatively high abundance in their esterified forms in neutrophil phospholipids (Yano et al 1983;Johnson et al 1999), it does not seem unreasonable to propose that either esterified DiHOMEs and/or esterified DHETs represent inhibitory signals with respect to the neutrophil NADPH oxidase activation, nor to speculate that other similar membrane-associated systems such as the plant NADPH oxidase or the mitochondrial respiratory chain are regulated in a similar fashion. 9(10)-/12(13)-EpOME stimulates the neutrophil respiratory burst.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, EETs influence neutrophil adherence in the low micromolar range (Pratt et al 2002). Since both arachidonate and linoleate are present in relatively high abundance in their esterified forms in neutrophil phospholipids (Yano et al 1983;Johnson et al 1999), it does not seem unreasonable to propose that either esterified DiHOMEs and/or esterified DHETs represent inhibitory signals with respect to the neutrophil NADPH oxidase activation, nor to speculate that other similar membrane-associated systems such as the plant NADPH oxidase or the mitochondrial respiratory chain are regulated in a similar fashion. 9(10)-/12(13)-EpOME stimulates the neutrophil respiratory burst.…”
Section: Discussionmentioning
confidence: 99%
“…Together, our findings support a role for lipid bodies to function as specific sites for eicosanoid formation. Of special interest for inflammatory cells where increased eicosanoid synthesis is observed, lipid body arachidonyl phospholipids might provide a source of substrate AA without requiring the perturbation of the integrity of membranes and could be replenished from the arachidonyl triglycerides abundant in lipid bodies (59,60).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of cells to low AA concentrations results in AA incorporation into primarily 1-acyl-linked phospholipid molecular species through a high affinity, low capacity enzymatic pathway. In contrast, exposure of cells to high levels of AA will result in the incorporation of AA into neutral lipid fractions (mainly TG) and the formation of 1,2-diarachidonoyl-sn-glycero-3-phosphocholine by a low affinity, high capacity pathway (42,71). Our data show that there is an increase in AA mass in the neutral lipid fractions of mast cells undergoing apoptosis.…”
Section: Discussionmentioning
confidence: 62%
“…AA Accumulation in Neutral Lipid Classes-Our previous studies suggested that inflammatory cells exposed to high concentrations of AA shuttled excess AA into neutral lipids, with triglycerides being the predominant class (42,43). To determine whether a similar pathway existed in BMMC, the neutral lipid fractions (Fig.…”
Section: Table Imentioning
confidence: 99%